Faktor-Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak Orang Pribadi - Rodhiyah, Ani; Estiningrum, Sri Dwi (E-Jurnal Akuntansi; Vol 32 No 5 (2022)DO - 10.24843/EJA.2022.v32.i05.p12, 2022)
The research was conducted with the aim of knowing the compliance factors of individual taxpayers in Boyolangu District, Tulungagung Regency. The variables in this research include Tax Amnesty, firmness of tax sanctions and knowledge of taxation. Where knowledge of taxation functions as a moderating variable between Tax Amnesty and the firmness of tax sanctions on individual taxpayer compliance variables. The data analysis technique used is multiple linear regression analysis and Moderated Regression Analysis (MRA) technique. The results of data analysis show that Tax Amnesty and the firmness of tax sanctions have no effect on taxpayer compliance, tax knowledge has a positive and significant impact on taxpayer compliance and Tax Knowledge can act as a moderator and can strengthen the relationship between Tax Amnesty and the firmness of tax sanctions on compliance. taxpayer. So that with knowledge of taxation as a moderator causes the effect of Tax Amnesty, and the firmness of tax sanctions on individual taxpayer compliance has a positive and significant influence. Keywords: Tax Amnesty; Firmness of Sanctions; Knowledge of Taxation; Taxpayer Compliance.